Brain structural changes in late-life generalized anxiety disorder. (30th October 2017) - Andreescu, Carmen; Tudorascu, Dana; Sheu, Lei K.; Rangarajan, Anusha; Butters, Meryl A.; Walker, Sarah; Berta, Rachel; Desmidt, Thomas; Aizenstein, Howard
Abstract: Late-life Generalized Anxiety Disorder (GAD) is relatively understudied and the underlying structural and functional neuroanatomy has received little attention. In this study, we compare the brain structural characteristics in white and gray matter in 31 non-anxious older adults and 28 late-life GAD participants. Gray matter indices (cortical thickness and volume) were measured using FreeSurfer parcellation and segmentation, and mean diffusivity was obtained through Diffusion Tensor Imaging (DTI). We assessed both macroscopic white matter changes [using white matter hyperintensity (WMH) burden] and microscopic white matter integrity [using fractional anisotropy (FA)]. No differences in macro- or microscopic white matter integrity were found between GAD and non-anxious controls (HC). GAD participants had lower cortical thickness in the orbitofrontal cortex (OFC), inferior frontal gyrus, and pregenual anterior cingulate cortex (ACC). Higher worry severity was associated with gray matter changes in OFC, ACC and the putamen. The results did not survive the multiple comparison correction, but the effect sizes indicate a moderate effect. The study suggests that late-life GAD is associated with gray matter changes in areas involved in emotion regulation, more so than with white matter changes. We conclude that anxiety-related chronic hypercortisolemia may have a dissociative effect on gray and white matter integrity. Highlights: Elderly GAD had lower cortical thickness in several frontal regions. Higher worry severity was associated with gray matter changes in the OFC and ACC. Late-life GAD is associated with more gray than white matter changes. Hypercortisolemia may have a dissociative effect on gray and white matter integrity.